An Exploratory Study on Service Quality Infrastructure in Malaysian Hotels - Qudratullah, Qudratullah; Malik, Ikmal Abd; Razak, Azrin Abdul; Derioh, Grace (Jurnal Minds: Manajemen Ide dan Inspirasi, 2023)
The purpose of this study is to explore the scope and the level of commitment among employees towards service quality management practises in a hotel's organisation. Descriptive research design is used to know the parameters of service quality management in hotels. By applying a mixed of qualitative and quantitative data collection method from 100 hotels in Kuala Lumpur, 54 hotels responded, resulting in a response rate of 45%. The results indicate that the design and monitoring functions were ranked as the two most important phases in the service management process to incorporate service quality practises into a hotel's infrastructure for improved service quality gap management, followed by the implementation and planning functions.